Biodegradable scaffolds designed to mimic fascia-like properties for the treatment of pelvic organ prolapse and stress urinary incontinence. (May 2016) - Roman, Sabiniano; Mangir, Naside; Bissoli, Julio; Chapple, Christopher R; MacNeil, Sheila
There is an urgent clinical need for better synthetic materials to be used in surgical support of the pelvic floor. The aim of the current study was to construct biodegradable synthetic scaffolds that mimic the three-dimensional architecture of human fascia, which can integrate better into host tissues both mechanically and biologically. Therefore, four different polylactic acid (PLA) scaffolds with various degrees of fibre alignment were electrospun by modifying the electrospinning parameters. Physical and mechanical properties were assessed using a BOSE electroforce tensiometer. The attachment, viability and extracellular matrix production of adipose-derived stem cells cultured on the polylactic acid scaffolds were evaluated. The bulk density of the scaffolds decreased as the proportion of aligned fibres increased. Scaffolds became stronger and stiffer with increasing amounts of aligned fibres as measured along the axis parallel to the fibre alignment. In addition, more total collagen was produced on scaffolds with aligned fibres and was organised in the direction of the aligned fibres. In conclusion, the electrospinning technique can be easily modified to develop biodegradable scaffolds with a spectrum of mechanical properties allowing extracellular matrix organisation towards human-like fascia.